Consumer Rights Act 2015(United Kingdom):Is it a good model in practising banking consumers from unfair terms in Islamic banking consumer contracts in Malaysia? = Consumer Rights Act 2015 (United Kingdom): Adakah ia model yang baik perlindungan konsumer perbankan daripada terma tidak adil dalam kontrak konsumer perbankan Islam di Malaysia? - Abu Bakar, Noor Mahinar; Mohd Yasin, Norhashimah; Razali, Siti Salwani (UKM Press, 2018)
As the Islamic banking industry becomes more advanced and complex, it is crucial that transactions in acquiring goods and services are reduced in writing of whatever terms and conditions agreed upon. These terms and conditions could potentially be deemed as unfair when relied on, would cause detriment (whether financial or otherwise) to banking consumers and, can cause significant imbalance in the rights and obligations of contracting parties. The objective of this article is to discuss the current flaws and highlight the inadequacies of consumer protection laws on unfair terms in consumer contracts in Malaysia. Findings in this study reveals that the abuse of power by the Islamic banks is due to one-sided contract which is not negotiated between the contracting parties. Furthermore, it is offered on a ‘take it or leave it’ basis and can make it difficult for banking consumers to discern risks in the contracts. Using content analysis and doctrinal legal method, this article analyses the potential of unfair terms in Islamic banking consumer contracts and to consider whether the wider scope of fairness and transparency assessment under the Consumer Rights Act 2015 (CRA) of the United Kingdom could provide a potential practical solution. Therefore, this article recommends that a statutory controlling mechanism such like the CRA of the United Kingdom, should be adopted to protect banking consumers from unfair contract terms in Malaysia. This article intends to contribute to policy priorities for the Malaysian government towards a better protection for banking consumers from unfair contract terms.